2019
DOI: 10.1002/esp.4646
|View full text |Cite
|
Sign up to set email alerts
|

Empirical observations and numerical modelling of tides, channel morphology, and vegetative effects on accretion in a restored tidal marsh

Abstract: Tidal marshes form at the confluence between estuarine and marine environments where tidal movement regulates their developmental processes. Here, we investigate how the interplay between tides, channel morphology, and vegetation affect sediment dynamics in a low energy tidal marsh at the Paul S. Sarbanes Ecosystem Restoration Project at Poplar Island. Poplar Island is an active restoration site where fine-grained material dredged from navigation channels in the upper Chesapeake Bay are being used to restore r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Plant productivity is also closely linked to marsh elevation with respect to high tide, tidal range, and sediment supply. Process‐based models coupling geomorphology and biology are therefore crucial tools for understanding salt marsh evolution (Fagherazzi, Fitzgerald, et al, 2013; Fleri et al, 2019).…”
Section: The Effect Of Vegetation On Hydrodynamics and Sediment Transmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant productivity is also closely linked to marsh elevation with respect to high tide, tidal range, and sediment supply. Process‐based models coupling geomorphology and biology are therefore crucial tools for understanding salt marsh evolution (Fagherazzi, Fitzgerald, et al, 2013; Fleri et al, 2019).…”
Section: The Effect Of Vegetation On Hydrodynamics and Sediment Transmentioning
confidence: 99%
“…Previous work highlights the strong ecogeomorphic feedbacks in these systems (Allen, 2000; Fagherazzi, Fitzgerald, et al, 2013; Kirwan & Megonigal, 2013; Nardin & Edmonds, 2014; Nardin et al, 2016; Temmerman et al, 2005). For example, vegetation influences hydrology, sediment erosion, deposition, and channel morphology (Fleri et al, 2019; Gran & Paola, 2001; Manners et al, 2015; Nepf, 2012). Marsh platform stabilization induced by vegetation can impact the migration of creek meanders, promotes single channelization, and reduces channel width (Simon & Collison, 2002).…”
Section: The Effect Of Vegetation On Hydrodynamics and Sediment Transmentioning
confidence: 99%
“…A follow‐up research also reported that the distribution of species and biomass in high salinity areas are affected by hydrological connectivity (Liu et al, 2020; Liu et al, 2020). As several other studies found that the distribution and cover rate of plant species are also influenced by the distribution and morphology of tidal creeks (Fleri, Lera, Gerevini, Staver, & Nardin, 2019; Wu et al, 2020), studies examining the relationship between dominant species population structure and hydrological connectivity remain to be limited.…”
Section: Introductionmentioning
confidence: 99%
“…According to the formation of plants, their mechanical properties and density, as well as their spatial distribution, can greatly affect the flow structure, biotic processes, channel planform and sediment movement in rivers [4,[37][38][39][40][41][42]. The effectiveness of plants as a bed reinforcing measure depends upon the scale and density, as well as the protrusion of plant stems that are partly or fully submerged, the geometric arrangement concerning one another, and their development stage [43,44].…”
Section: Introductionmentioning
confidence: 99%